Nowcasting Finnish GDP growth using financial variables: a MIDAS approach - Olli-Matti Laine; Annika Lindblad (Bank of Finland, 2020)
We analyse the performance of financial market variables in nowcasting Finnish quarterly GDP growth. Especially, we assess if prediction accuracy is affected by the sampling frequency of the financial variables. Therefore, we apply MIDAS models that allow us to forecast quarterly GDP growth using monthly or daily data without temporal aggregation in a parsimonious way. Our results show that financial market data nowcasts Finnish GDP growth relatively well. When it comes to individual variables, ratios like average price-to-earnings, average price-to-book or average dividend yield track GDP growth well. Our results suggest that the sampling frequency of financial market variables is not crucial: the forecasting accuracy of daily, monthly and quarterly data is similar.
urn:nbn:fi:bof-202005132138
Keywords: E44; G00; E37; 330; MIDAS; Nowcasting; Financial markets; GDP